ANALYSIS OF THE CAUSES OF COMPANY PERFORMANCE IN FAMILY COMPANIES IN THE MANUFACTURING INDUSTRY - Elisa, Elisa; Cahyadi, Hadi (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this study was to obtain empirical evidence on the effect of family ownership, firm size, firm age, family involvement on the board of commissioners, and family involvement on the board of directors on firm performance. In this study, secondary data was used tested using SPSS version 21. This study used data on manufacturing companies listed on the Indonesia Stock Exchange from the period 2017-2019, as many as 28 family companies engaged in the manufacturing sector that has been selected using the purposive sampling method with a total of 84 data for three years. The results showed that family ownership and firm size had a significant positive effect on firm performance. In contrast, firm age, family involvement on the board of commissioners, and family involvement on the board of directors had no effect on firm performance.